IMPLEMENTASI PERATURAN PEMERINTAH NOMOR 82 TAHUN 2001 DALAM KAITANNYA DENGAN PENCEMARAN AIR PADA BUDI DAYA IKAN SEGAR OLEH MASYARAKAT DI BENDUNGAN WAY RAREM - ANSORI ANSORI; BAMBANG SETIAWAN (Universitas Bandar Lampung (UBL), 2021)
Water management is not as easy as imagined because water as one of the natural resources in it has the potential to trigger conflicts in people's lives, such aswater pollution in the Way Rarem Dam as a result of fresh fish farming by the community . The problem is how to implement Government Regulation No. 82 of 2001 in relation to water pollution in fresh fish farming by the community in Way RaremDam, North Lampung? and what are the inhibiting factors in the implementation ofGovernment Regulation Number 82 of 2001 in relation to water pollution in fresh fishfarming by the community in Way Rarem Dam North Lampung? The research method isthrough a normative juridical approach and an empirical approach using secondarydata and primary data, then qualitative data analysis is carried out . The results of thestudy, that the implementation of Government Regulation No. 82 of 2001 in relation towater pollution in fresh fish farming by the community in the Way Rarem Dam, NorthLampung has been carried out in accordance with the laws and regulations, includingthe planning, implementation, monitoring and evaluation stages using the approachecosystem as well as to carry out repairs and guidance to cage fishermen at Way RaremDam and the inhibiting factors in the implementation of Government Regulation No. 82of 2001 in relation to water pollution in fresh fish farming by the community in WayRarem Dam, North Lampung, among others, the available budget is not yet available.insufficient, non-functioning sports facilities as they should, lack of cooperation and communication between Regional Apparatus Units, low community participation, employee discipline and lack of facilities and infrastructure.